2021
DOI: 10.3390/app11125559
|View full text |Cite
|
Sign up to set email alerts
|

Association of Self-Rated Pain with Clinical Peri-Implant Parameters and Cytokine Profile in Smokers and Never Smokers with and without Peri-Implantitis

Abstract: To examine the association between self-perceived pain (SPP), clinical and radiographic peri-implant parameters, and biomarker levels among smokers and never smokers with and without peri-implantitis. Sixty individuals (20 smokers with peri-implantitis [group-1], 20 never smokers with peri-implantitis [group-2] and 20 never smokers without peri-implantitis [control-group]) were included. SPP was evaluated using a numeric pain rating scale (NPRS). Peri-implant plaque index (PI), probing depth (PD), and bleeding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Moreover, this result supports the hypothesis that CSF-1 increases bone loss, which is one of the differential consequences of periodontitis. Tissue destruction in periodontitis indicates an insufficient resolution of inflammation as a result of immune cell dysfunction, which is another potential indicator of the role of CSF-1 in periodontal diseases [ 27 28 ]. Ma et al [ 29 ] concluded that IL-34 might be associated with inflammation in periapical lesions in chronic apical periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, this result supports the hypothesis that CSF-1 increases bone loss, which is one of the differential consequences of periodontitis. Tissue destruction in periodontitis indicates an insufficient resolution of inflammation as a result of immune cell dysfunction, which is another potential indicator of the role of CSF-1 in periodontal diseases [ 27 28 ]. Ma et al [ 29 ] concluded that IL-34 might be associated with inflammation in periapical lesions in chronic apical periodontitis.…”
Section: Discussionmentioning
confidence: 99%